2021
DOI: 10.2196/25706
|View full text |Cite
|
Sign up to set email alerts
|

Benefiting From Digital Use: Prospective Association of Internet Use With Knowledge and Preventive Behaviors Related to Alzheimer Disease in the Israeli Survey of Aging

Abstract: Background Previous work documented the beneficial association between internet use and improved cognition, functional capacity, and less cognitive decline among people in late adulthood. This work focused on potential mechanisms of such an association: knowledge on Alzheimer disease (AD) and preventive behaviors related to AD. Objective The aim of this study was to examine prospective associations of internet use and perceived computer skills with know… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
1
2
0
Order By: Relevance
“…Lastly, in line with previous literature [ 81 , 82 ], we found that Internet use was associated with an uptake of preventive behaviors. However, due to the limitations of the SHARE database, we could not investigate which specific digital activities are associated with enhanced uptake of preventive behaviors in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, in line with previous literature [ 81 , 82 ], we found that Internet use was associated with an uptake of preventive behaviors. However, due to the limitations of the SHARE database, we could not investigate which specific digital activities are associated with enhanced uptake of preventive behaviors in our sample.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, research suggests that stigma against dementia is related to fear and a lack of understanding about the disease [ 20 , 46 ]. Consequently, there is a growing need for dementia education and awareness campaigns targeted toward digital media [ 47 ] and specifically toward Twitter and other social media platforms.…”
Section: Discussionmentioning
confidence: 99%
“…However, continuously monitoring these biomarkers is unfeasible as obtaining these data incurs either high cost (eg, MRI) or great inconvenience for the patients due to the invasive nature of the procedure [15][16][17]. Digital markers, however, that evaluate cognitive impairment by analyzing behavioral data collected from digital devices such as smartphones [18][19][20] or personal computers [21][22][23] could alleviate the above challenges and would provide an inexpensive, easy-to-use alternative. To this end, the development and validation of digital markers that allow for the reliable screening of MCI is an important research topic [17,24,25].…”
Section: Introductionmentioning
confidence: 99%